The Role of Video Content in The New York Times and The Guardian’s Coverage of the Israeli War on Gaza - Kreishan, Asem (Žurnalistikos tyrimai, 2024)
The Israel-Hamas conflict has received widespread coverage from global media sources. The coverage has been extensive, including both conventional news channels and social media platforms, and includes a vast range of opinions and tales. Social media has substantially impacted the dissemination of knowledge, as seen by platforms such as TikTok, which have accumulated billions of views on material relating to this topic. The research revealed a significant discrepancy in the number of postings supporting Palestine compared to those supporting Israel. The battle has resulted in the dissemination of deceptive information and misinformation. Hamas has been prohibited from the majority of social media networks; however, its propaganda continues to flow on channels like Telegram. Local content artists in Gaza recorded their experiences and garnered substantial followings. The study investigates the utilization of video material by newspapers, with a specific emphasis on four key aspects: the characteristics of the content, the intended audience, video editing techniques, and the influence of this content on worldwide public perception. Video coverage in the New York Times strives to provide a fair and equitable portrayal of the Israeli and Palestinian perspectives, including conflicts and fatalities from all sides. The newspaper’s objective is to provide extensive coverage that emphasizes the plight of both parties, however, it has faced criticism for not sufficiently illuminating the agony endured by the Palestinians.